2010
DOI: 10.1371/journal.pone.0015446
|View full text |Cite
|
Sign up to set email alerts
|

The Way to a Man's Heart Is through His Stomach: What about Horses?

Abstract: BackgroundHow do we bond to one another? While in some species, like humans, physical contact plays a role in the process of attachment, it has been suggested that tactile contact's value may greatly differ according to the species considered. Nevertheless, grooming is often considered as a pleasurable experience for domestic animals, even though scientific data is lacking. On another hand, food seems to be involved in the creation of most relationships in a variety of species.Methodology/Principal FindingsIn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 29 publications
3
34
1
1
Order By: Relevance
“…These results confirm those obtained in terms of learning performance on these same horses by Sankey et al (2010c): FR horses were the only ones to showed an increase of performance over sessions. Grooming reward was associated with more inattentive visual responses (i.e., head orientation towards the environment) and no decrease of “agitated” behavior (i.e., moving forward or backward).…”
Section: Discussionsupporting
confidence: 92%
“…These results confirm those obtained in terms of learning performance on these same horses by Sankey et al (2010c): FR horses were the only ones to showed an increase of performance over sessions. Grooming reward was associated with more inattentive visual responses (i.e., head orientation towards the environment) and no decrease of “agitated” behavior (i.e., moving forward or backward).…”
Section: Discussionsupporting
confidence: 92%
“…The existence of reciprocal bonds between humans and pets has been firmly established (Prato-Previde et al, 2006; Parthasarathy & Crowell-Davis, 2006; Nagasawa et al, 2009a,b), but the role of tactile stimulation is unclear. In fact, a study in horses showed that grooming was not sufficient for the establishment of a bond, while feeding was (Sankey et al, 2010). Perhaps tactile stimulation in horses is not rewarding, whereas eating certainly is.…”
Section: Discussionmentioning
confidence: 99%
“…This was only found when the horses were subject to complex training systems that required a horse to learn and process multiple pieces of information at once, and seemed to not be true for simple avoidance or association tasks (Kusunose and Yamanobe, 2002). Horses rehabilitated or trained using positive reinforcement (as opposed to negative reinforcement) techniques tend to have lower training times, higher motivation to participate in training, engage in more exploratory behaviour, appear to perceive training and humans (both familiar and unfamiliar) more positively, have increased memory, and display less problem behaviours during training sessions (McCall, 2007;Warren-Smith and McGreevy, 2007;Innes and McBride, 2008;Sankey et al, 2010a;Sankey et al, 2010b;Slater and Dymond, 2011). The type of reinforcement used and the training environment appear to play a role in a horse's perception of humans (Sankey et al, 2010c;Baragli et al, 2011) This is consistent with findings in other animals (Desmond and Laule, 1994;Hiby et al, 2004;Laule and Whittaker, 2007).…”
Section: The Relationship Between Horse Cognition Training and Welfarementioning
confidence: 99%
“…When combined with the evidence that positive reinforcement appears to be beneficial for training and the human-horse relationship (Sankey et al, 2010a), this suggests that some of the popular cultural beliefs surrounding horse trainability may be incorrect and in need of further investigation.…”
Section: The Relationship Between Horse Cognition Training and Welfarementioning
confidence: 99%